2005
DOI: 10.1007/s10653-004-5741-x
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in surface sediments and benthic organisms from Guaymas Bay, east coast of the Gulf of California

Abstract: In order to know the concentration of mercury in surface sediments, macroalgae and clams from Guaymas Bay, Mexico, 20 surface sediment samples and several individuals of Codium amplivesciculatum (3), Enteromorpha clathrata (4), Gracilaria subsecundata (2), Ulva lactuca (2), Chione subrugosa (80) and Crassostrea gigas (40) were collected and their Hg concentration was measured by a cold vapor Hg analyzer, after acid digestion. In addition, granulometric analysis and quantification of total organic carbon, alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…3). Similar patterns of Hg distribution (higher levels in sediments from the vicinity of metal sources) have been reported in Patos lagoon, Brazil (Mirlean et al 2003) and Guaymas lagoon, Mexico (Green-Ruiz et al 2005). On the other hand, in a previous study in Coatzacoalcos estuary, lowest values of Cd, Cr and Pb were detected in sediments from sites located upstream of Minatitlán (Páez-Osuna et al 1986).…”
Section: Surficial Sedimentssupporting
confidence: 79%
“…3). Similar patterns of Hg distribution (higher levels in sediments from the vicinity of metal sources) have been reported in Patos lagoon, Brazil (Mirlean et al 2003) and Guaymas lagoon, Mexico (Green-Ruiz et al 2005). On the other hand, in a previous study in Coatzacoalcos estuary, lowest values of Cd, Cr and Pb were detected in sediments from sites located upstream of Minatitlán (Páez-Osuna et al 1986).…”
Section: Surficial Sedimentssupporting
confidence: 79%
“…In addition, Green-Ruiz at al. [27] found moderate to strong contamination of Hg (measured by cold vapor AAS) via ER and geochemical index values of sediments collected in the same bay.…”
Section: Marine Sedimentsmentioning
confidence: 81%
“…Several studies have observed significant correlations between metal(oid) contents and fine-grain sediments (silts and clays), which is due to the high specific surface area and the TOC content of the sediments (r silt-TOC = 0.84; r clay-TOC = 0.68). These factors lead to metal(oid)s being trapped in sediments and natural soils (Horowitz and Elrick 1987;Moore et al 1989;Ergin et al 1996;FernandezCaliani et al 1997;Tam and Wong 2000;Zhang et al 2002;Reddy et al 2004;Green-Ruiz et al 2005).…”
Section: Resultsmentioning
confidence: 99%